A complexidade da memória e do esquecimento na sociedade em rede: os paradigmas digitais - Ferreira, Nelson (2017)
Memory combined with the capacity for rationalization and the development of recording techniques played a fundamental role in the development of the human species and resulted in the capacity to create various technological devices that conditioned profound changes in people's way of life. The object of the investigation is the study of information technology impacts and its reflexes on individual and collective memory, as well as to analyze if the digital paradigms result in the need for a re-reading of memory and forgetfulness in the information society. In order to fulfill this desideratum, a bibliographical review of the authors that deal with memory and its relations with silence, forgetfulness and violence in contemporary society is carried out, and these themes are confronted with the reality imposed by the communication through the digital platform, to the end of the research analyze the recent scientific publications regarding memory and forgetfulness in society.